Constitutional court of the Azerbaijanian republic - Рустамзаде, Айхан Х. о. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
In the article are studied legal principles of handling with an individual complaint to the ConstitutionalCourt of Azerbaijanian Republic. It is underlined in the article that a right on a constitutional complaint is theconcrete form of realization of right of judicial defence. Maintenance and form of serve of individual complaintis examined in the Constitutional Court of Azerbaijanian Republic.